Analisi Socioeconomica Meccanismi di Deforestazione e Effetti Ambientale nella Regione Kisangani, DR-Congo - Mashala B, Bwama Meyi Marcel; Ciminello R, Pieter, M. (European Journal of Sustainable Development, 2017)
Reducing Emissions coming from deforestation and forest degradation is internationally recognized as an important mechanism for mitigating climate change. DR Congo is one of the target countries of this mechanism. The study we propose has two objectives: - the relationship between immediate and underlying causes and deforestation rates; - identification of the socio-economic characteristics of the actors (multinationals and rural households). The study also identifies the different types of timber harvested by determining their corresponding quantities and the impact of exploitation on biodiversity. Methodological approach: participatory surveys and empirical survey combined with geo-forestry analysis using GPS throughout the different axes of the eastern province. Among the techniques used are: Focus group; interview; Case study and GPS coordinate collection. Present and future effects are also the subject of this study with reference to the methods applied in deforestation.